IMUNOGENISITAS VAKSIN INAKTIF WHOLE CELL Aeromonas salmonicida PADA IKAN MAS (Cyprinus carpio) - Setyawan, Agus; Hudaidah, Siti; Ronapati, Zulfikar Zafeskan; Sumino, Sumino (AQUASAINS, 2012)
The aims of this research was to determine the immunogenicity of inactivated vaccine A. salmonicida whole cell in common carp and the best mothod in vaccine administration. Vaccine was produced by inactivated A. salmonicida with adding 1 ppm (v/v) formaldehide and incubated for 24h in room temperature. Ten juvenil of carp (Vaccine was administrated in each 10 fish by injection intraperitoneally (107 cfu/fish), orally (107 cfu/fish), immersion (107 cfu/ml for 30 minute) and control (fish with no vaccination). Booster was conducted 7 days after first vaccination with same dossage and method. Titer antibody was evaluated in three times i.e. before vaccination, 7th days after first vaccination, and 7th days after booster. Water quality such as dissolved oxygen, pH, and water temperature was measured as a supported parameters. Results showed that titer antibodi for all treatment before vaccination was 1/6. However, titer antibody after vaccination and booster increased to 1/58.67 and 1/85.33 for i.p injection, 1/42.67 and 1/64 for oral, 1/24 and 42.67 for immerse, respectively. Whereas, there was no significantly increasing of titer antibody in control that was 1/9.33 and 1/18.67 for vaccination and bosster, respectively. Vaccine adminsitration method by injection i.p. was the best method for obtain the best immunogenicity of vaccine. Water quality parameters along this experiment still in optimum range for common carp living.